Efficacy of Curry Leaf Powder and Tomato Paste on Storage Stability of Chicken Meat Patties - Reddy, B. Obula; Rao, B. Eswara; Mallika, E. Naga; Rao, T. Srinivasa; Reddy , G.V. Bhaskar (Journal of Meat Science, 2015)
A study was conducted to investigate the effect natural antioxidants i.e. of curry leaf powder and tomato paste comparing with synthetic antioxidant (butylated hydroxyl anisole) on the quality and storage stability of chicken meat patties added with 5 per cent oat flour at refrigeration (4±1°C) temperature. Storage studies revealed a significant (p<0.05) effect on the physico-chemical, microbiological and sensory quality of chicken meat patties due to the incorporation of various antioxidants during refrigeration. Chicken meat patties incorporated with tomato paste at 5 per cent level had significantly (p<0.05) lower values for cooking loss, pH, standard plate count and yeast and mould count and significantly (p<0.05) higher values for various attributes of sensory evaluation under refrigerated storage. Chicken meat patties added with curry leaf powder at 1 per cent level had significantly (p<0.05) lower values for 2-TBARS than control and other treatments. A significant (p<0.05) increase in cooking loss, pH and 2-TBARS value and a decrease in emulsion stability, WHC of chicken meat patties was observed as refrigeration storage period progressed. Psychrophilic and Coliforms were not detected in any of the treatments and control sample during storage. It is concluded that tomato paste at 5 per cent level exerted significantly (p<0.05) desirable effect on quality characteristics of chicken meat patties and protected its quality with a higher degree of acceptability.